2008
DOI: 10.1007/s00270-008-9339-z
|View full text |Cite
|
Sign up to set email alerts
|

When Coughing Can Cause Stroke—A Case-Based Update on Cerebral Air Embolism Complicating Biopsy of the Lung

Abstract: Introducing gas to the circulation is a largely iatrogenic problem which can result in serious morbidity and even death. We report a case of CT-guided needle biopsy of a pulmonary lesion complicated by acute stroke. The English literature on cerebral air embolism is reviewed, including an update of current opinions on its pathomechanism, diagnostic findings, therapeutic strategies, and means of prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…All patients were seen again by the radiologist in a final consultation two to four hours after the biopsy for a control CT scan, but there are no systematic records of this talk. Unfortunately, there is no record of the probably very important factor "coughing" [27]. Finally, it must be stated that not CT, but transesophageal and probably transcutaneous echocardiography must be considered the gold standard diagnostic measure.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were seen again by the radiologist in a final consultation two to four hours after the biopsy for a control CT scan, but there are no systematic records of this talk. Unfortunately, there is no record of the probably very important factor "coughing" [27]. Finally, it must be stated that not CT, but transesophageal and probably transcutaneous echocardiography must be considered the gold standard diagnostic measure.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of symptomatic air embolism, based on the present and previously reported cases, are summarized in the following section (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In the majority of cases, the clinical symptoms of air embolism occur either during or immediately following needle biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have indicated that pathological pulmonary abnormalities may predispose a patient to an increased risk of air embolism (12,24). It is believed that, following lung biopsy and needle withdrawal, a large number of alveolar-venous or bronchial-venous fistulas can develop along the needle trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, transpulmonary puncture carries the potential risk of causing systemic air embolism, as is the case with lung biopsy. 6,7 We think a percutaneous transhepatic approach through the diaphragmatic fi stula, which has not been previously reported, has the advantage to avoid these risks of the transpulmonary approach for treating such cases.…”
Section: Discussionmentioning
confidence: 99%